FXR activation prevents liver injury induced by Tripterygium wilfordii preparations. (3rd June 2021) - Peng, Wan; Dai, Man-Yun; Bao, Li-Juan; Zhu, Wei-Feng; Li, Fei
Abstract: Tripterygium glycosides tablets (TGT) and Tripterygium wilfordii tablets (TWT) are the preparations of Tripterygium wilfordii used to treat rheumatoid arthritis (RA) in the clinic, but the hepatotoxicity was reported frequently. This study aimed to determine the potential toxicity mechanism of liver injury induced by the preparations of Tripterygium wilfordii in mice. Here, we performed metabolomic analysis, pathological analysis and biochemical analysis of samples from mice with liver injury induced by TGT and TWT, which revealed that liver injury was associated with bile acid metabolism disorder. Quantitative real-time PCR (QPCR) and western blot indicated that the above changes were accompanied by inhibition of farnesoid X receptor (FXR) signalling. Liver injury from TWT could be alleviated by treatment of the FXR agonist obeticholic acid (OCA) via activation of the FXR to inhibit the c-Jun N-terminal kinase (JNK) pathway and improve bile acid metabolism disorder by activating bile salt export pump (BSEP) and organic solute-transporter-β (OSTB). The data demonstrate that FXR signalling pathway plays a key role in T. wilfordii -induced liver injury, which could be alleviated by activated FXR. These results indicate that FXR activation by OCA may offer a promising therapeutic opportunity against hepatotoxicity from the preparations of T. wilfordii .